2011
DOI: 10.1007/s12239-011-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

Automotive windshield — pedestrian head impact: Energy absorption capability of interlayer material

Abstract: During accident, the interlayer of windshield plays an important role in the crash safety of automotive and protection of pedestrian or passenger. The understanding of its energy absorption capability is of fundamental importance. Conventional interlayer material of automotive windshield is made by Polyvinyl butyral (PVB). Recently, a new candidate of high-performance nanoporous energy absorption system (NEAS) has been suggested as a candidate for crashworthiness. For the model problem of pedestrian head impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…This is expected since the glass sheet with thicker PVB layer would absorb more impact energy via molecule vibration and friction by the interlayer as polymer-like material, verified by Ref. [45]. As the Rayleigh wave velocity c R % 3370 m/s [46], which is sufficiently high for the initiation velocity v 0 .…”
Section: Effect Of Pvb Thicknessmentioning
confidence: 88%
See 1 more Smart Citation
“…This is expected since the glass sheet with thicker PVB layer would absorb more impact energy via molecule vibration and friction by the interlayer as polymer-like material, verified by Ref. [45]. As the Rayleigh wave velocity c R % 3370 m/s [46], which is sufficiently high for the initiation velocity v 0 .…”
Section: Effect Of Pvb Thicknessmentioning
confidence: 88%
“…Martinez et al [44] reported that the capability for transmitting the impact energy depends on the thickness and type of the adhesive used. Therefore, the variation in PVB thickness will have a great effect on delaying the passage of the elastic wave into the backing glass layer and reducing the amplitude and the wavelength of wave through internal friction [45], which results in reducing the maximum radial crack speed as show in Fig. 9.…”
Section: Effect Of Pvb Thicknessmentioning
confidence: 99%
“…In particular, effective absorption of mechanical energy at low-impact speed, i.e., below 100 m/s is of great interest [5,6]. As one of the major branches of fullerene family, the carbon nanotube (CNT) has demonstrated an outstanding mechanical energy dissipation ability through water-filled CNT [7], CNT forest and bundle [7], CNT/epoxy nanocomposites [8], CNT immersed in nonaqueous liquid [9], intercalating vertical alignment with aligned existing layered compounds [10], and sponge-like material containing self-assembled interconnected CNT skeletons [11], among others.…”
Section: Introductionmentioning
confidence: 99%
“…The crashworthiness of optimum designs with conventional steel and advanced high-strength steel were compared using the full vehicle analysis. Xu et al (2011) compared the energy absorbing abilities of high-performance nanoporous energy absorption system (NEAS) interlayer and polyvinyl butyral interlayer for windshield by conducting the simulations of windshield and pedestrian head impact. They concluded that NEAS interlayer may absorb more energy than PVB interlayer.…”
Section: Introductionmentioning
confidence: 99%